Publisher Correction: Quasi zenith satellite system-reflectometry for sea-level measurement and implication of machine learning methodology - Kutubuddin Ansari; Hong_Woo Seok; Punyawi Jamjareegulgarn (My University, 2023)
Figure 6.Daily sea-level changes (unit: m) obtained from QZSS L1
Keywords: Reflectometry; Zenith; Synthetic Aperture Radar (SAR) Applications and Techniques